2021
DOI: 10.1038/s42003-021-02279-8
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion of the diabetes candidate gene Slc16a13 in mice attenuates diet-induced ectopic lipid accumulation and insulin resistance

Abstract: Genome-wide association studies have identified SLC16A13 as a novel susceptibility gene for type 2 diabetes. The SLC16A13 gene encodes SLC16A13/MCT13, a member of the solute carrier 16 family of monocarboxylate transporters. Despite its potential importance to diabetes development, the physiological function of SLC16A13 is unknown. Here, we validate Slc16a13 as a lactate transporter expressed at the plasma membrane and report on the effect of Slc16a13 deletion in a mouse model. We show that Slc16a13 increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 69 publications
0
13
1
Order By: Relevance
“…The expression of SLC16A13 and SLC2A1 was higher in LUAD tissues and their expression was associated with a poorer prognosis, so these two genes might be oncogenic. SLC16A13 is a lactate transporter expressed at the plasma membrane and a potential target for the treatment of type 2 diabetes and non-alcoholic fatty liver disease ( Schumann et al, 2021 ), while its role in tumor needs to be further explored. SLC2A1 , also known as glucose transporter type 1 (GLUT1), is well characterized in cancer and is associated with tumor progression and metastasis ( Yan et al, 2015 ; Nagarajan et al, 2017 ; Xiao et al, 2018 ), including in LUAD where is has previously been shown to be upregulated and associated with poorer prognosis ( Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of SLC16A13 and SLC2A1 was higher in LUAD tissues and their expression was associated with a poorer prognosis, so these two genes might be oncogenic. SLC16A13 is a lactate transporter expressed at the plasma membrane and a potential target for the treatment of type 2 diabetes and non-alcoholic fatty liver disease ( Schumann et al, 2021 ), while its role in tumor needs to be further explored. SLC2A1 , also known as glucose transporter type 1 (GLUT1), is well characterized in cancer and is associated with tumor progression and metastasis ( Yan et al, 2015 ; Nagarajan et al, 2017 ; Xiao et al, 2018 ), including in LUAD where is has previously been shown to be upregulated and associated with poorer prognosis ( Guo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond drug transporters, genetic variants in other transporters not generally involved in drug absorption or disposition have been associated with plasma levels of various endogenous solutes, including a number of amino acids, oligopeptides, neurotransmitters, and heavy metals 35–38 . Many of these solutes are not routinely measured in a clinical care setting and, therefore, cannot be used in observational studies.…”
Section: Clinical Transporter Researchmentioning
confidence: 99%
“…37 Recently, follow-up studies have shown that the orphan transporter SLC16A13, which is located next to SLC16A11 on chromosome 17p13.1, is a lactate transporter and also plays a role in type 2 diabetes. 38 • Using knockout mice, riboflavin was identified as the major substrate of SLC22A14, which was an orphan at the time. 39 Detailed studies showed that riboflavin plays an important role in the testis and reduced uptake of riboflavin in male SLC22A14 knockout mice resulted in infertility.…”
Section: • Using Metabolomic Genomewide Association Studies (Gwas)mentioning
confidence: 99%
See 2 more Smart Citations